In vitro culture establishment of Hibiscus sabdariffa L.: obtaining seedlings and induction of callus under different culture conditions aiming at biomass accumulation (Research, Society and Development, 2021)
Hibiscus sabdariffa L., is a plant that belong to the family Malvaceae Juss., popularly known as vinagreira, the species has pharmacological importance. The in vitro culture of callus represents an important resource for the continuous production of high quality medicinal compounds, being possible the production of biomass with compounds of medicinal interest. The present work aimed to verify the necessary cultivation conditions for the highest production of wet callogenic mass of explants (hypocotyls and roots). The explants were inoculated in different basic culture media (MS and B5) supplemented with different concentrations of growth regulators and kept in a B.O.D incubator at 30ºC, photoperiod of 16 h of light. Callus production was evaluated by measuring the wet weight of callus after 120 days of cultivation. Based on the results obtained in the study, it can be observed that the proliferation of H. sabdariffa, callus occurred regardless of the type of explants, basal media or concentrations of growth regulators, 2,4-D and BAP, but the best results for the production of callogenic masses of hypocotyls and roots were in MS medium supplemented with 0,1 mg.L-1 of 2,4-D in combination with 0,1 mg.L-1 of BAP (T2), presenting averages of callogenic masses from hypocotyl explants (7,43 ± 0.19 g) and roots (6,75 ± 0.07 g).  The results show that in vitro techniques have advantages of biomass production in sterile and controlled environmental conditions, allowing a better control of the development processes and production of tissues rich in bioactive compounds.